Development of numerical model of interaction of the wind turbine to darya with the wind stream in the u-v-p variables (International Journal of Mathematics and Physics, 2013)
The use of natural eco-friendly energy, such as wind, due to the use of wind energy devices [1-3]. Thisthesis is a theoretical study of the interaction of the rotating turbine Darrieus-type H-rotor wind flow. The paperconsiders the interaction of a uniform wind flow with a rotating wind turbine Darrieus-type H-rotor, based on theNavier-Stokes equations, which is supplemented by members which take into account the lift and the drag force. Thenumerical solution of the equations in the variables u-v-p. The results obtained and the development of his methodsof analysis will be useful for the design work for the creation of industrial designs windmill carousel.